Personality and career aspirations of high school students - Uy, Alejandro Abaya
This is a descriptive study of high school students' career aspiration and career personality orientation. It explored the factors that influence career choice and decision for guidance counseling and parent education purposes. Three schools, a science high school, arts and science high school, and a laboratory high school, were purposively selected as sampling areas for student respondents. A total of 75 students were requested to answer the career personality orientation questionnaire. The data were analyzed using descriptive and discriminant analysis statistics. Results show that the students' personality orientations are consistent with the nature of their high school curriculum. Students from both the science high school and arts and science high school are described as investigative, social, and artistic. The students from the laboratory schools are described as social, investigative and artistic. If the personality orientations are to be viewed according to gender, both male and female respondents are described as investigative, social and artistic and personality as well. The primary factor influencing students' career choices if their personal preference. The socio-cultural influence would come next with the family, school, and then friends/peers, respectively. Gender was not perceived as influencing career choice. It also showed that when the students' career personality orientation is matched with their first career aspiration, 38.7% students have a correct match. There is however a higher percentage of match between students' career personality orientation and their second choice of career (53.3%).